О семантической и синтаксической валентноcти английского глaгола bеаt - Дзидоликене, Вита (Kalbotyra, 1990)
The different lexical meanings of the verb “to beat” have two basic semantic components: 1 - motion (a) intensive (of different intensity) b) directed, c) repeated (single); 2 - momentary contact. Each lexical meaning possesses a finite number of basic and differential semantic components. They determine how definite lexical meanings can combine with other words in the sentence. In three of its lexical meanings the verb “beat” has 3 actants and in four others it has 2 actants on the semantic level. On the syntactic level two actants are obligatory. In combinations with nouns such as “pulse”, “heart”, “sun”, “rain”, “beat” is normally used with one actant. The rust obligatory actant is the agent of the situation, the second is the patient of the situation. The third non-obligatory actant has the function of instrument.